Activity of ceftazidime (GR 20263) against nosocomially important pathogens. - Hamilton-Miller, J M (1981)
Ceftazidime was considerably more active than cefuroxime against 180 strains of resistant species of nosocomial gram-negative bacteria. In terms of antibacterial spectrum and intrinsic activity, ceftazidime is an improvement upon existing beta-lactam antibiotics in clinical use and can be regarded as a possible alternative to gentamicin.